2017
DOI: 10.1111/nep.13009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sustained low efficient dialysis versus continuous renal replacement therapy on renal recovery after acute kidney injury in the intensive care unit: A systematic review and meta‐analysis

Abstract: This systematic review examines the impact of sustained low-efficiency dialysis or continuous renal replacement therapy on patient outcomes in critically ill patients with acute kidney injury. Meta-analysis indicated no statistically significant difference in the primary outcome of overall renal recovery (risk ratio 0.87, 95% confidence interval 0.63-1.20, I2 66%). There appears to be no clear advantage for continuous renal replacement in the haemodynamically unstable patient; however, there may be a mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Results regarding to comparison in renal recovery, in-hospital mortality, and in-ICU mortality between AKI patients given CRRT and those given SLED were corresponding to previous studies 4,30 published in recent years. According to previous studies, worse baseline renal function and more frequent intradialytic hypotension were associated with lower likelihood of renal recovery.…”
Section: Discussionsupporting
confidence: 53%
“…Results regarding to comparison in renal recovery, in-hospital mortality, and in-ICU mortality between AKI patients given CRRT and those given SLED were corresponding to previous studies 4,30 published in recent years. According to previous studies, worse baseline renal function and more frequent intradialytic hypotension were associated with lower likelihood of renal recovery.…”
Section: Discussionsupporting
confidence: 53%
“…Fluid accumulation is an independent risk factor for poor prognosis in MOF, and CRRT has been shown to be superior at overall fluid removal compared to IHD [13]. Sustained low-efficiency dialysis (SLED) has comparable haemodynamic outcomes and can be considered in MOF [48].…”
Section: Modality Of Rrtmentioning
confidence: 99%
“…Despite these theoretical advantages of hemofiltration, the data on this issue is inconclusive. However, the hemodynamic instability during dialysis is not that relevant in clinical practice, especially in the Age of hybrid procedures like sustained low efficiency dialysis (SLED) [ 180 , 181 , 182 , 183 ]. In this context, observational studies have shown a tendency towards improved renal recovery under continuous hemofiltration, whereas a recent meta-analysis (excluding observational studies) and RCTs showed no difference [ 184 , 185 , 186 , 187 ].…”
Section: Potential Harm Of Renal Replacement Therapymentioning
confidence: 99%